Redução de cloreto de sódio em carnes marinadas bovina e de frango : qualidade da carne, composição química e aspectos microbiológicos - Carvalho, Camila Barbosa (2013)
Meat and meat products are important sources of protein, fat, amino acids, minerals, vitamins and other nutrients (Biesalski, 2005). In recent years, consumer demand for a food safer and better quality of meat and meat products with reduced levels of fat, sodium chloride, cholesterol , nitrite plus a composition improved in profile fatty acids, incorporating functional ingredients, grown worldwide (Scollan et al, 2006; Hocquette et al, 2012) Sodium is considered an important marker of quality of food. The Ministry of Health recommends that the content of this nutrient in the diet does not exceed 2300 mg for adults. However, the population mean of sodium intake in Brazil exceeds 3200 mg. The consumption of pizza, processed meats, industrialized snacks, stuffed cookie and soda has been linked to high intakes of sodium and more than 70% of the population consumes quantities above the maximum tolerable intake for sodium. In the category of manufactured products, meat and meat products represent the second largest contribution in sodium intake in the diet, proximately 20.8% of the daily sodium intake. The higher contribution of sodium comes from processed meat products (0.54g), with only 0.05g of sodium from fresh meat (Jiménez- Colmenero et al., 2001). The use of salt substitutes such as potassium chloride is limited primarily by its bitter taste. Therefore, various compounds bitter taste inhibitors have been proposed mainly to be added in the parameter flavor objects may be further study including the use of masking the bitter taste, for example, herbs and spices (Carraro et al. 2012). For these reasons, partial substitution of sodium chloride by potassium chloride and addition of aromatic herbs, and spices coloríficos marinated meat products becomes an utput promising for the reduction of sodium and maintaining the palatability of these products. This study aimed to develop marinated meats (beef and chicken) using low-sodium seasonings complete, replacing sodium chloride by potassium chloride in percentages of 25 and 50% with the addition of herbs and spices.We used four types of meat to perform the analyzes, 2 types (bovine Longissimus dorsi and Quadricepsfemoris) and 2 types of chicken (drumstick and breast fillet). Loin The - Longissimus dorsi was acquired in the cattle production sector in Cutting Experimental Farm Iguatemi (FEI) belonging to the State University of Maringá (UEM), Brazil. The duckling - Quadriceps femoris was purchased from Maria Macia Agricultural Cooperative Mista, Campo Mourao-Pr, Brazil. The chicken were purchased from Poultry Slaughterhouse Canção, Maringa-Pr, Brazil, belonging to the same batch. The herbs and spices were purchased from a local market in Maringa-Pr, Brazil. The spices were used for marinated garlic (Allium sativum), annatto (Bixa orellana), turmeric (Curcuma longa), chilli (Capsicum frutescens), black pepper (Piper nigrum), oregano (Oreganum vulgare) and Marjoram (Oreganum majorana) . The reagents were analytical grade, belonging to the laboratory of Food Engineering - UEM, Brazil. The marination of the meat was applied statically, using 2g spice to 100g of meat, dip the meat in seasoning, when ingredients penetrate gradually by diffusion, without the application of force for 24 hours kept at 4ºC and packed vacuo. Meat moisture and ash were determined according to (ISO-R-1442, 1997) and (ISO-R-936, 1998). Crude protein were obtained according to (ISO-R-937, 1978) and total fat was determined according to (ISO-R- 1443, 1973). As regards the mineral composition analysis, samples were digested by dry method (AOAC, 1990) and the contents of sodium and potassium were quantified on a AA240FS atomic absorption spectrophotometer (Varian, USA) in mg per kg of mineral product, using standard analytical solutions and curves. Microbiological analyzes were performed for thermo-tolerant coliform and Salmonella sp, determined using methodology determines by Silva et al (1997). The pH was measured 24 hours after thawing of the meat marinade for all samples. A portable Crisson 503 pH-meter equipped with a penetration probe electrode was used to measure pH of the samples, in triplicate. The cooking loss was calculated as the difference between the weight of the samples thawed and baked (% CL = [weight (thawed - cooked weight) / thawed] x 100). The mechanical properties of meat has been obtained by texture analysis using Stable Micro Systems Taxt Plus (Texture Technologies Corp., UK) with a load cell of 5.00 kg and a Warner- Bratzler (WB). The analysis was performed according to the methodology proposed by the Research Center of the USDA Meat Animal (Wheeler et al., 1997). The determination of color was measured after 24 hours storage of the product at 5°C marinated by colorimetry. For the analysis of the color, the samples were grilled until reaching an internal temperature of 70°C. Lipid oxidation was assessed in duplicate by the method of measuring the quantity of 2-thiobarbituric acid (TBA) (Raharjo et al. 1992), using 5 g of milled raw meat sample. The sensory test in this study was approved by the Ethics Committee for Human Research at the State University of Maringá, CAAE File No. 0389-11 and performed with 100 untrained hypertensive and 40 admitted to a local hospital, using hedonic scale of 9 points.Statistical analyzes were performed by analysis of variance (ANOVA) and Bonferroni averaging (Berthold et al., 2011) at a significance level of 5% by Statistics 7.0 (SAS, 2004).To beef of all microbiological treatments fulfilled the recommendations given by Brazilian legislation for seasoned meats. Levels of moisture, ash, protein and fat did not differ between treatments. These levels according to normality for beef (Torres et al., 1998). The replacement of sodium by potassium, herbs and spices in marinades reduced the level of sodium in 47.5% of samples from the longissimus dorse muscle and 45.1% in the quadriceps femoris muscle (Duckling) for the treatment F50. The color of meat with regard to brightness (L *), redness (a *) and yellowness (b *) were similar for all samples. The cooking losses were on average 30%, within the normal range for seasoned meats. A significant difference was observed between treatments only with regard to texture the quadricepsfemoris, probably due to the presence of the cut nerve. As to the results of sensory analysis for beef, the acceptability index remained above 70% for all samples and reached 80% for bovine duckling when the sodium content was replaced by 50%. The results are considered excellent and entirely acceptable with regard to sensory attributes, second Dutcosky (2011). For the chicken all treatments reached the microbiological specifications of the Brazilian legislation for chicken marinade with Salmonella and maximum value of 104 for coliforms at 45 º C (Silva et al., 2005). For the physico-chemical properties of chicken meat marinated with sodium reduction was no statistical difference between the samples on moisture, ash, crude protein and total lipid. The samples showed a significant difference (p <0.05) in levels of sodium and potassium between control and F50 for the two types of chicken cuts. There was a significant reduction in sodium between samples, reduction of 51.06% for chicken drumstick and 50.71% for chicken breast fillet compared to the control treatment and F50, a percentage above 50 % reduction due to the addition of herbs and spices for seasoning, which corresponds to 17% of the total composition, and the added ingredients (Allium sativum, Oreganum Majorana, Curcuma longa, Piper nigrum) did not contain significant levels of sodium its composition (TACO, 2011). Significant difference in color was observed for the filet of chicken breast between treatments F25 and F50. This is probably due to the use of the spice turmeric-long causing a higher concentration of yellowish color. Although there was no significant difference (p <0.05) among treatments for both types of meat in relation to weight loss after cooking the chicken drumsticks had higher rates on this factor, due to the high content fat compared to beef and chicken breast. Texture values remained stable between treatments. There was no significant difference between samples for pH and TBARS, and the analyzed parameters remained within the normal range and similar to the results found by Harder et al. (2010) for chicken with annatto a mean pH of 6.47 and Torres et al. (1998) with an average pH to 6.54 with spices chicken burger, similar to the values of this study. Rates of 1.84 mg malonaldehyde /kg-1 TBARS were also reported by the same authors, after 15 days of storage of the product. The results of sensory evaluation indicate that all samples tested had acceptability index above 70%. The chicken drumstick with a 50% reduction in sodium content was potentially accepted by consumers, reaching 80% of acceptability. Replacement of 25 to 50% sodium chloride by potassium chloride in beef and chicken marinated products with herbs and spices, proved to be a highly effective strategy to achieve acceptable products, without altering its microbiological, sensorial, chemistry and physics.